PENGARUH SIKAP, NORMA SUBYEKTIF DAN KOMITMEN ORGANISASI TERHADAP NIAT UNTUK MELAKUKAN WHISTLEBLOWING - Sindy Angrayni; Resti Yulistia; Arie Frinola Minovia; Dandes Rifa (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2021)
Everyone can become a whistleblower, but they face an ethical dilemma, whether they have to disclose the fraud that they know or not. The purposes of this study were to examine the effect of attitude, subjective norms and organizational commitment on whistleblowing intention. Data were collected using questionnaires and analyzed using multiple linear regressions. The samples of this study were 85 respondents from BPK RI and BPKP West Sumatera. The results showed that subjective norms have positive effect on the intention of whistle-blowing action, while organizational commitment has no effect on whistleblowing intention. Surprisingly, this study found attitude has negative effect on the intention of whistle-blowing action. It means the better attitude, the lower the whistleblowing intention.